Surgical treatment of corneal perforation by auto tissue: a clinical case - E. A. Ivachev (Российский офтальмологический журнал, 2018)
Purpose: to analyze the effectiveness of therapeutically covering cornea perforation in a cancer patient with auto conjunctiva. Material and methods. A patient with a diagnosis of cancer of the right kidney pT1N0M1, ST 4, metastasis in the left kidney and L 1-2 vertebrae; cancer rectum pT3N0M0, liver metastases in the form of a hypodense focus underwent several surgeries: radical nephrectomy of the right kidney; anterior resection of the rectum; atypical liver resection (S3, S4, S5). Over the 5-year period of treatment in an oncology hospital the patient received 48 courses of immunotherapy (the most recent session took place in June 2014). Starting from September 2014, the patient was treated for keratouveitis of both eyes. The vision of both eyes dropped drastically from 1.0 to 0.01 (uncorrected) in just 2 months. On April 6, 2015 the patient was admitted to the Ophthalmological hospital, diagnosed with corneal ulcer perforation complicated by a cataract of the right eye, corneal dystrophy of the cornea, and complicated cataract of the left eye. He was treated by covering corneal perforation with a flap of autoconjunctiva and blepharorhaphy of the right eye. Results. In the right eye, a vascularized wall-eye in the lower third of the cornea with a stable plugging effect was formed. On Sept. 24, 2015 (5.5 months after autoconjunctiva covering and blepharorrhaphy), cataract phacoemulsification with implantation of an intraocular lens in the right eye was performed (at the date of discharge, uncorrected OD vision was 0.1 not correct). On Nov. 23, 2015 the same procedure was repeated in the left eye (at discharge vis OS = 0.4 uncorrected). After 1.5 years, the vision remained stable (OD = 0.1, OS= 0,4 uncorrected). Conclusion. The clinical case demonstrates a high risk of corneal ulcer perforation in cancer patients caused by reduced immunity after chemotherapy. Eye preserving coverage of corneal perforation with an autoconjunctiva flap accompanied by blepharorhaphy showed a satisfactory result of sealing the perforation of the cornea. The vascularized wall-eye formed affected the optical part of the cornea with minimal losses, which later allowed performing a cataract extraction with the restoration of visual functions. For citation: Ivachev E.A. Surgical treatment of corneal perforation by auto tissue: a clinical case. Russian ophthalmological journal. 2018; 11 (1): 80-4. doi: 10.21516/2072-0076-2018-11-1-80-84 (In Russian).